Evaluation of Preemergence Herbicide Programs for Control of Protoporphyrinogen Oxidase-Resistant Amaranthus palmeri in Soybean - Michael M. Houston; L. Tom Barber; Jason K. Norsworthy; Trent L. Roberts (International Journal of Agronomy)
Protoporphyrinogen oxidase- (PPO-) resistant Amaranthus palmeri (S.) Wats. (Palmer amaranth) was confirmed in Arkansas in 2015. Field trials were conducted in Crawfordsville, Gregory, and Marion, Arkansas in 2016, and Crawfordsville and Marion in 2017, assessing PPO-resistant Palmer amaranth control options in Glycine max (L.) Merr. (soybean). Twelve trials consisted of 26 preemergence (PRE) treatments, evaluated for Palmer amaranth control and density reduction at 28 days after treatment (DAT). Treatments that consisted of PPO- or acetolactate synthase- (ALS-) inhibiting herbicides such as flumioxazin (72 g ai ha−1) or sulfentrazone + cloransulam (195 g ha−1 + 25 g ha−1) controlled Palmer amaranth <60%. At 28 DAT, treatments including mixtures of a very-long-chain fatty acid (VLCFA) plus the photosystem II- (PSII-) inhibiting herbicide metribuzin provided increased control over single herbicide sites of action (SOA) or herbicides mixtures to which Palmer amaranth was resistant. Pyroxasulfone + metribuzin (149 g ha−1 + 314 g ha−1) controlled Palmer amaranth 91% control across twelve trials at 28 DAT. S-metolachlor alone did not provide consistent, acceptable control of PPO-resistant Palmer amaranth (55–77%); subsequent research has determined that these populations are resistant to S-metolachlor. A minimum of two effective herbicides should be included in soybean PRE programs for control of PPO-resistant Palmer amaranth.